Betting the house: Australia’s uninsured and underinsured households and the climate crisis - Thrower, Jack (My University, 2025)
Over 800,000 Australian homes are not fully insured, including many with mortgages. This poses serious risks to both homeowners and the broader economy. The increasing frequency and intensity of climate disasters, which are driving up the cost of insurance, are exacerbating the problem. Taxing fossil fuel companies and investing in a National Climate Disaster Fund would help keep Australians safe from physical risks and financial ruin.
Keywords: Housing, communities and neighbourhoods; Income, wealth and finances